What the market does not kill: an analysis of spieciesist morality and economics - Wesley Felipe de Oliveira; Alessandro Pinzani (INTERthesis, 2015)
In this paper we discuss the relation between morality and economy starting with Michael Sandel’s analysis of the moral limits of the market. Sandel investigates how moral values are increasingly being included within the logic of market economy guided by profit. We investigate particularly how the speciesist morality that justifies the exclusion of animals from the moral community is bound to the logic of market, including and keeping nonhuman animals within a system that seeks monetary profit through their exploration and commercialization. We defend that although the economy has a significant influence in determining certain moral practices, the opposite is also true, i.e., morality can also exert an influence on the market and dictate its limits regarding what may or may not be submitted to the logic of economic profit. The overcoming of speciesist morality through ethical proposals to include sentient beings in the sphere of moral actions and to take their interests into account, could – so our conclusion – lead to free animals from the market logic.